Six-minute walk test in cardiac rehabilitation - M. G. Bubnova; A. L. Persiyanova-Dubrova (Кардиоваскулярная терапия и профилактика, 2020)
Six-minute walk test (6MWT) is a simple and safe tool for assessing exercise tolerance in  various  categories  of  patients.  Currently,  6MWT  is  used to assess the functional status of a patient and determine the strategy of increasing physical activity, primarily in patients with reduced exercise tolerance and contraindications for cardiopulmonary exercise  test. The basic requirements for the 6MWT are presented, taking into account the factors affecting its  informativeness  and  accuracy,  as  well  as the interpretation of results. The diagnostic and prognostic value of 6MWT in different categories of patients are discussed. The prospects for 6MWT use in cardiac rehabilitation for planning rehabilitation program, prescribing exercises,  determining  the  risk   of   complications,   and   evaluating the effectiveness  are  considered.  The  limitations  of  6MWT  and  ways to overcome it, as well as directions for further research are presented.